Crack control method for tunnel molded lining concrete

By establishing a temperature stress simulation model and optimizing the construction process, crack-resistant concrete is prepared, and the problem of shrinkage and cracking of railway tunnel lining concrete is solved, and the temperature-deformation regulation of tunnel lining concrete is achieved, which improves the durability and safety of the structure and avoids the Repair afterwards.

CN119266862APending Publication Date: 2025-01-07SOUTHEAST UNIV +2

Patent Information

Application Number
CN202310820207.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The cracking problem caused by shrinkage deformation of railway tunnel secondary lining concrete is difficult to effectively solve during construction and service, affecting the durability and safe operation of the structure. The existing technology mainly adopts post-repair measures, which is difficult to fundamentally solve the problem.

Method used

By establishing a finite element calculation model for temperature stress simulation, optimizing working conditions parameters and construction technology, we prepare crack-resistant concrete, including hydration temperature rise inhibitors, calcium-magnesium composite expansion agents, mineral blends, etc., to control the adiabatic temperature rise of concrete and Self-shrinkage strain, adjust the mold entry temperature and mold removal and maintenance process, realize the dual temperature-deformation control of tunnel lining concrete to prevent cracking.

Benefits of technology

It achieves precise crack prevention and control before the tunnel lining concrete pouring, reduces the risk of cracking, improves the durability and safety of the structure, avoids the cost and complexity of post-repair, and ensures the long-term operation of railway tunnels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119266862A_ABST
    Figure CN119266862A_ABST
Patent Text Reader

Abstract

The invention discloses a crack control method for tunnel molded lining concrete. The crack control method comprises the following steps that a temperature stress simulation finite element calculation model is established according to the size of a tunnel lining structure; analyzing lining concrete cracking risk coefficients corresponding to different working condition parameter optimization combinations through a temperature stress simulation finite element calculation model; the anti-crack concrete is prepared by uniformly mixing and stirring the hydration temperature rise inhibitor, the calcium-magnesium composite expanding agent, the mineral admixture, the cement, the gravel and the water according to a certain proportion. After construction of the tunnel inverted arch and the inverted arch filling layer is completed, the mold entering temperature in the working condition parameters is adjusted and controlled, and the prepared anti-crack concrete is poured on the inverted arch at a time to form a lining concrete layer; and after anti-crack concrete pouring is completed, formwork removal and moisturizing maintenance after formwork removal are conducted according to the formwork removal time representing the formwork removal maintenance technology and the parameter requirements for maintenance after formwork removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete detection, and in particular relates to a crack control method for tunnel cast lining concrete. Background Art

[0002] With the continuous advancement of infrastructure construction, the layout of the railway network is becoming more and more perfect. However, in the process of large-scale construction and operation, we often face the situation of changing construction terrain and complex service environment. High-quality railway tunnel construction has become an important part of railway tunnel construction. Railway tunnels generally adopt composite lining structures, and the secondary lining concrete structure is the main structure to bear the bottom pressure, prevent surrounding rock deformation, and ensure the long-term durability of the tunnel. Therefore, ensuring the safe and durable service of the secondary lining concrete of the railway tunnel is an important guarantee for the long-life and normal operation of the railway tunnel.

[0003] However, the practice of tunnel projects that have been built and are under construction shows that most tunnel projects have different degrees of defects, and cracking of the tunnel secondary lining concrete due to shrinkage deformation is one of the most important defects. Problems such as water seepage and durability damage caused by cracking seriously affect and threaten the safe operation of the railway system. The prevention and control of tunnel lining cracks has always been a recognized problem at home and abroad. The study of concrete cracking is a frontier science that integrates building underground engineering and chemical engineering, and there are many problems that need to be solved urgently. Therefore, based on the construction and service characteristics of the secondary lining concrete of railway tunnels, a technical method for dealing with shrinkage cracking of concrete structures is proposed, which is of great significance to improving the durability of railway engineering tunnel lining concrete and ensuring the safe and long-term operation of railway tunnels.

[0004] Generally, the design strength grade of railway tunnel lining concrete is high, and there are problems such as high cementitious material consumption, high insulation temperature rise and large shrinkage. Although the thickness of the secondary lining concrete layer is not large, the internal temperature of the lining concrete still has the characteristics of high temperature rise and rapid temperature drop during the construction process; secondly, the tunnel lining is constrained by the lower invert arch, surrounding rock, etc. due to its early shrinkage and deformation during the construction period, and there is a greater risk of cracking. This is mainly manifested in that the lining concrete is strongly constrained by the cast-in-place invert arch structure and the one-time casting length is long. The shrinkage during the cooling process is constrained, which can easily cause through cracks, thereby increasing the risk of cracking and affecting the durability of the structure.

[0005] To solve the shrinkage cracking of railway tunnel lining concrete, existing research has proposed some methods, such as:

[0006] Chinese invention patent application CN202110564257 discloses a permanent repair method for tunnel lining cracks using UHPC materials. This method seals the cracked tunnel lining concrete with UHPC grouting, which can achieve good repair effects.

[0007] Chinese invention patent application CN202121432745 provides a structure for treating water seepage from cracks in tunnel linings. By setting drainage holes, water seepage from cracks is drained to drainage ditches to ensure the waterproof effect of the tunnel;

[0008] Chinese invention patent application CN202210458194 discloses a high-performance rapid repair material for tunnel lining cracks, which mainly repairs cracks that have already opened by using high-performance crack repair materials;

[0009] Chinese invention patent application CN201720593726 discloses a tunnel lining crack repair device, which locates cracks through the coordination of equipment to achieve precise pouring repair of cracks.

[0010] From the above analysis, it can be seen that most of the existing patents control concrete cracks through tunnel lining construction measures, process optimization and post-repair methods. However, it is essentially difficult to effectively solve the shrinkage problem after concrete pouring through construction measures, process optimization and post-repair methods, especially for strongly constrained structures such as railway tunnel composite linings, which cannot fundamentally solve the problem. More importantly, compared with ordinary concrete structures, railway tunnel lining concrete has a more severe and changeable special service environment, and has extremely high durability requirements. The non-cracking of the lining is a necessary guarantee for quality tunnel engineering. Summary of the invention

[0011] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for controlling cracking of tunnel cast lining concrete.

[0012] To achieve the above object, the present invention is implemented by adopting the following technical solutions:

[0013] The present invention provides a method for controlling cracks in tunnel cast lining concrete, which further comprises the following steps:

[0014] Determine the material parameters, mechanical parameters, thermal parameters, structural parameters and environmental parameters, and establish a finite element calculation model for temperature stress simulation according to the tunnel lining structure dimensions based on the coupling of multiple factors including concrete temperature stress shrinkage, concrete autogenous shrinkage and invert rigidity constraint;

[0015] The lining concrete cracking risk coefficient corresponding to the optimal combination of different working condition parameters is analyzed by the temperature stress simulation finite element calculation model, so as to select the optimal combination of different working condition parameters with the cracking risk coefficient less than the cracking threshold value, wherein the working condition parameters include the adiabatic temperature rise, the autogenous shrinkage strain value, the mold entry temperature, and the demolding time and post-demolding curing process, which characterize the demolding curing process;

[0016] According to the adiabatic temperature rise and autogenous shrinkage strain values ​​that characterize the performance of concrete in the working condition parameters, the hydration temperature rise inhibitor, calcium-magnesium composite expansion agent, mineral admixture, cement, sand and gravel and water are mixed and stirred in a certain proportion to obtain crack-resistant concrete;

[0017] After the tunnel invert and the invert filling layer are constructed, the mold entry temperature in the control working condition parameters is adjusted to pour the prepared crack-resistant concrete onto the invert at one time to form a lining concrete layer;

[0018] After the anti-cracking concrete is poured, the formwork is removed and the post-formwork moisturizing curing is carried out according to the parameters of the formwork removal time and post-formwork curing that characterize the formwork removal and curing process.

[0019] Furthermore, the anti-cracking concrete comprises the following components by mass percentage:

[0020] 450-500 parts of cementitious materials, 665-785 parts of sand, 1030-1190 parts of crushed stone and 145-180 parts of water;

[0021] The gelling material comprises the following components by mass percentage:

[0022] 1-2% hydration temperature rise inhibitor, 6-10% calcium-magnesium composite expansion agent, 30-50% mineral admixture, and the rest is cement.

[0023] Furthermore, the gelling material comprises:

[0024] The cement is P·Ⅱ42.5 silicate cement;

[0025] Fly ash is Class F II or above;

[0026] The slag powder is S95 grade slag powder;

[0027] The hydration temperature rise inhibitor has a cement hydration heat reduction rate of ≥30% 24 hours after initial setting and a cement hydration heat reduction rate of ≤15% 7 days after initial setting;

[0028] The calcium-magnesium composite expansion agent comprises the following components by mass percentage: 50% to 70% of CaO and 30% to 50% of light-burned MgO, wherein the reaction activity value of the light-burned MgO is 100 to 180s.

[0029] Furthermore, the mass ratio of fly ash to slag powder in the mineral admixture is 3:1.

[0030] Furthermore, the mold entry temperature is ≤28°C, the slump of the crack-resistant concrete is controlled to be 180-220mm, and the air content is 4%-6%.

[0031] Furthermore, the cracking threshold is controlled within 0.7.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1) The method for controlling cracks in tunnel cast lining concrete provided by the present invention can accurately prevent and control cracks in advance through numerical modeling calculation results before pouring tunnel lining. Based on the model calculation cracking assessment and combined with the existing construction conditions, the concrete performance and construction process are optimized and adjusted to achieve the purpose of accurately implementing crack control;

[0034] 2) The problem of cracking of railway tunnel lining concrete is fundamentally solved through prior process adjustment, so that there will be no leakage caused by cracking after the lining concrete is poured. Compared with most existing post-repair measures, it is safer, has no repair and maintenance costs, and is more operational and implementable, ensuring the safe and long-term operation of railway tunnels;

[0035] 3) Adding hydration temperature rise inhibitor and calcium-magnesium composite expansion agent to the poured concrete can reduce the cement hydration temperature rise rate and effectively supplement the early and mid-to-late shrinkage of concrete. Combined with the preliminary calculation simulation, concrete performance and construction technology, it can achieve dual control of temperature and deformation of tunnel lining concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A tunnel entity finite element calculation model provided by an embodiment of the present invention;

[0037] Figure 2 A tunnel lining temperature calculation cloud diagram provided by an embodiment of the present invention;

[0038] Figure 3 A tunnel lining stress calculation cloud diagram provided by an embodiment of the present invention;

[0039] In the figure:

[0040] 1. Inverted arch structure; 2. Inverted arch filling; 3. Lining structure. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0042] Example

[0043] An embodiment of the present invention provides a method for controlling cracks in tunnel cast lining concrete, comprising the following steps:

[0044] Determine the material parameters, mechanical parameters, thermal parameters, structural parameters and environmental parameters, and establish a finite element calculation model for temperature stress simulation according to the tunnel lining structure dimensions based on the coupling of multiple factors including concrete temperature stress shrinkage, concrete autogenous shrinkage and invert rigidity constraint;

[0045] The lining concrete cracking risk coefficient corresponding to the optimal combination of different working condition parameters is analyzed by the temperature stress simulation finite element calculation model, so as to select the optimal combination of different working condition parameters with the cracking risk coefficient less than the cracking threshold value, wherein the working condition parameters include the adiabatic temperature rise, the autogenous shrinkage strain value, the mold entry temperature, and the demolding time and post-demolding curing process, which characterize the demolding curing process;

[0046] According to the adiabatic temperature rise and autogenous shrinkage strain values ​​that characterize the performance of concrete in the working condition parameters, the hydration temperature rise inhibitor, calcium-magnesium composite expansion agent, mineral admixture, cement, sand and gravel and water are mixed and stirred in a certain proportion to obtain crack-resistant concrete;

[0047] After the tunnel invert and the invert filling layer are constructed, the mold entry temperature in the control working condition parameters is adjusted to pour the prepared crack-resistant concrete onto the invert at one time to form a lining concrete layer;

[0048] After the anti-cracking concrete is poured, the formwork is removed and the post-formwork moisturizing curing is carried out according to the parameters of the formwork removal time and post-formwork curing that characterize the formwork removal and curing process.

[0049] In this embodiment, if Figure 1 As shown, this embodiment provides a simulation finite element calculation model for the crack control process of railway tunnel lining concrete structure. Through numerical model calculation, the crack control performance of railway tunnel lining is analyzed, and based on the principle that no through shrinkage cracks appear in the lining structure, based on the model calculation and analysis results, the control requirements for the preparation and process technology of crack-resistant concrete are proposed.

[0050] Firstly, according to the railway tunnel lining construction process, combined with the material properties, theoretical formulas, design data, etc. of the lining structure, the material parameters, mechanical parameters, thermal parameters, structural parameters and environmental parameters required for numerical simulation calculation are reasonably determined, and a simulation finite element calculation model is established based on the actual structural form of the railway tunnel lining;

[0051] Secondly, with different performance concrete mix ratios, mold entry temperature, ambient temperature, one-time pouring length, thickness, formwork type, trolley demolding time, and maintenance methods as variables, the cracking risk coefficient of different working condition combinations is calculated and analyzed, and the calculation results are analyzed to obtain key control indicators. Combined with the actual working conditions at the construction site, the working condition combination that meets the crack control requirements is selected;

[0052] 1.1 Simulation finite element calculation model

[0053] A numerical model is established based on the coupling of multiple factors such as concrete temperature stress shrinkage, concrete autogenous shrinkage, and rigid constraints of the invert on the lining. The corresponding cracking risk coefficient value is calculated through the model working condition. When the cracking risk coefficient is within 0.7, it means that the structure has a 95% non-cracking guarantee rate and basically will not crack. When the cracking risk coefficient value is greater than 0.7, the structure has a greater cracking risk, and the larger the value, the higher the risk of structural cracking. When the value exceeds 1.0, it is bound to crack.

[0054] 1.1.1 Establishment of finite element calculation model

[0055] According to the actual size of the tunnel lining, a finite element calculation model for temperature stress simulation is established. Figure 1 As shown, it includes an invert 1, an invert filling layer 2 and a lining 3.

[0056] 1.1.2 Determination of calculation parameters

[0057] The calculation parameters are selected based on the calculation model, including material parameters in Table 1, mechanical parameters in Table 2, thermal parameters in Table 3, structural parameters in Table 4, and environmental parameters in Table 5. Each parameter is obtained according to the requirements of the corresponding specifications and test results to maximize the consistency between the calculation parameters and the actual working condition parameters. A certain benchmark working condition is selected for comparison, and different parameters are obtained to show the temperature strain changes of the calculation model.

[0058] Table 1

[0059]

[0060] Table 2

[0061] project unit Parameter Value Value basis Concrete compressive strength MPa 1,3,5,7,14,28d Test results Splitting tensile strength MPa 1,3,5,7,14,28d Test results Autogenous shrinkage strain value με 0~28d continuous data Test results Creep 1 0~28d continuous data Test results

[0062] Table 3

[0063]

[0064]

[0065] Table 4

[0066]

[0067] Table 5

[0068] project unit Parameter Value Value basis Tunnel ambient temperature ℃ 30 On-site testing Humidity in the tunnel % 85 On-site testing

[0069] In this embodiment, the lining concrete cracking risk coefficient corresponding to different operating parameter optimization combinations is analyzed by a temperature stress simulation finite element calculation model to select different operating parameter optimization combinations with cracking risk coefficients less than the cracking threshold.

[0070] 1.2 Calculation and analysis of different working conditions

[0071] 1.2.1 Analysis of temperature-stress calculation results

[0072] Based on the modeling results, the temperature-stress changes inside the concrete from the tunnel lining structure to the pouring were analyzed. Figure 2 As shown in the figure, the temperature of the annular lining structure is mainly concentrated in the center, while the concrete surface far away from the center and close to the formwork is relatively low, and the temperature difference between the inside and outside is obvious. Figure 3 As shown in the figure, near the construction joint of the invert, the shrinkage of the lining concrete is affected by the first cast invert structure, and the stress is most concentrated here, which is the place with the greatest risk of cracking in the entire lining structure.

[0073] 1.2.2 Calculation parameters of the benchmark condition

[0074] The benchmark working condition is taken as the analysis and comparison object. The benchmark working condition is shown in Table 6. The temperature stress change of the lining concrete is calculated to obtain the cracking risk coefficient value of the lining structure under the benchmark working condition.

[0075] Table 6

[0076]

[0077]

[0078] Note: The autogenous shrinkage strain value “+” indicates that the concrete is in an expansion state, and “-” indicates that the concrete is in a contraction state.

[0079] 1.2.2 Calculation parameter combinations for other working conditions

[0080] Optimize the concrete mix performance, change the mold entry temperature, demolding time and maintenance after demolding, obtain different working condition combinations, compare the model calculation results with the benchmark working condition calculation results, and analyze and select the calculation parameter combination that meets the anti-cracking risk factor. Table 7 shows the calculation parameter combination of other working conditions, which is based on the changes of the basic working conditions.

[0081] Table 7

[0082]

[0083] 1.3 Analysis of cracking risk under different working conditions

[0084] 1.3.1 Analysis of concrete performance conditions

[0085] On the basis of the basic working conditions, the temperature-stress variation law of the lining and the maximum cracking risk coefficient after changing the concrete performance working condition parameters are compared. Based on the size law of each influencing factor, the main influencing factors and key controls are finally determined. Table 8 is a summary of the comparison of structural temperature, stress and maximum cracking risk coefficient.

[0086] Table 8

[0087]

[0088] The adiabatic temperature rise of concrete and the temperature of entering the mold directly affect the maximum temperature rise and the peak temperature. Reducing the adiabatic temperature rise and the temperature of entering the mold can effectively reduce the risk coefficient of structural cracking. Similarly, the smaller the shrinkage value of concrete, even in an expanded state, the greater the maximum stress value and the maximum cracking risk coefficient. However, it should be noted that the single working condition optimization shown in Table 8 cannot solve the cracking problem. The cracking risk coefficient after single working condition optimization is still above 1.0. Given that the structure itself has an extremely high risk of cracking, a combination of multiple working condition optimizations is required to ensure that the cracking risk coefficient is within 0.7.

[0089] 1.3.2 Analysis of demoulding and curing process conditions

[0090] On the basis of the basic working conditions, the variation law of lining temperature stress and the maximum cracking risk factor after changing the working condition parameters of the demolding and curing process are compared. Table 9 is a summary of the comparison of structural temperature, stress and maximum cracking risk factor.

[0091] Table 9

[0092]

[0093] Under the benchmark working condition, the cracking risk coefficient of the lining structure is bound to crack when it exceeds 1.0. As shown in Table 8, the cracking risk coefficient can be reduced by 10% when the adiabatic temperature rise of concrete is reduced from 51℃ to 45℃; the cracking risk coefficient can be reduced by 20% when the autogenous shrinkage strain value of concrete is optimized from -150με to +150με; the cracking risk coefficient can be reduced by 16% when the concrete mold entry temperature is reduced from 35℃ to 25℃; in addition, as shown in Table 9, when the demolding time is extended from 1d to 5d, the cracking risk coefficient can be reduced by 9%; the curing after demolding can be reduced by 6% and 8% respectively from no curing to moisturizing or covering geotextile. As shown above, the structural cracking risk coefficient can be reduced to a certain extent by reducing the adiabatic temperature rise and mold entry temperature, optimizing concrete autogenous shrinkage, extending the demolding time and strengthening curing, but it is impossible to ensure that the cracking risk coefficient is within 0.7 when a single working condition is selected, and various working conditions need to be implemented in combination. As an implementation case of the invention, combined with the actual needs of the project and the feasibility on site, in order to ensure that the cracking risk coefficient is within 0.7, the best solution selected working condition two (concrete adiabatic temperature rise of 45°C), working condition five (concrete shrinkage deformation is not less than +150με), working condition seven (mold entry temperature is not greater than 28°C), working condition nine (3d demolding) and working condition eleven (watering every 24 hours within 14 days). The process combination can reduce the cracking risk coefficient by 54%, and the cracking risk coefficient can be controlled within 0.7. The above-mentioned combined working conditions have low cost and strong comprehensive feasibility. The target working condition parameters are summarized in Table 10.

[0094] Table 10 Summary of target operating parameters

[0095]

[0096] In this embodiment, after establishing a temperature stress simulation finite element calculation model and optimizing the combination analysis of parameters under different working conditions, according to the requirements of selecting concrete performance, demolding process, etc., a method for controlling cracks in formwork lining concrete of a railway tunnel specifically includes the following steps:

[0097] S1: Mix and stir the hydration temperature rise inhibitor, calcium-magnesium composite expansion agent, mineral admixture, cement, sand and gravel and water in proportion to obtain crack-resistant concrete;

[0098] The crack-resistant concrete includes the following components by mass percentage: 450-500 parts of cementitious materials, 665-785 parts of sand, 1030-1190 parts of crushed stone and 145-180 parts of water;

[0099] The cementitious material includes the following components by mass percentage: 1-2% of hydration temperature rise inhibitor, 6-10% of calcium-magnesium composite expansion agent, 30-50% of mineral admixture, and the rest is cement;

[0100] S2: After the construction of the inverted arch 1 and the inverted arch filling layer 2 is completed, the anti-cracking concrete of step S1 is poured onto the inverted arch at one time, and is solidified to form a lining concrete layer 3;

[0101] S3: After the anti-cracking concrete is poured, the formwork is removed 3 days later, and the surface of the lining concrete layer is subjected to 14 days of moisturizing maintenance.

[0102] According to a large amount of calculation and monitoring data as well as on-site test analysis, the demolding time for crack-resistant concrete is 3. When the demolding takes place, the interior of the concrete is in the final stage of temperature drop, and the temperature difference between the inside and outside of the concrete after demolding is less than 20°C.

[0103] In addition, the formwork during the period of formwork can prevent the rapid evaporation of water on the concrete surface during the early high-temperature hydration stage, avoid drying shrinkage cracks, and ensure the strength and durability of the concrete. Therefore, choosing 3D demolding can not only ensure the construction quality but also ensure the turnover speed of the mold. The 14-day maintenance after demolding can adjust the moisturizing maintenance frequency according to the actual situation of the anti-cracking concrete surface of the tunnel lining.

[0104] In this embodiment, the method for determining the dosage of concrete hydration temperature rise inhibitor is as follows:

[0105] Table 11 Dosage of concrete hydration temperature rise inhibitor

[0106] Serial number serial number Hydration temperature rise inhibitor dosage 1 CTRI0 0% 2 CTRI0.5 0.5% 3 CTRI1.5 1.0% 4 CTRI1.5 1.5% 5 CTRI2.0 2.0% 6 CTRI2.5 2.5% 7 CTRI3.0 3.0%

[0107] The hydration heat reduction rate of concrete hydration temperature rise inhibitor is expressed as the ratio of the difference between the hydration heat of cement in the reference mortar and the hydration heat of cement in the tested mortar within the specified age to the hydration heat of cement in the reference mortar. Based on the cement dosage, 300% standard sand, 40% water and a certain proportion of concrete hydration temperature rise inhibitor are mixed according to Table 10. The temperature change inside the mortar is directly measured in a constant temperature environment using a calorimeter for the evenly mixed mortar, and the hydration heat at different ages is calculated. In addition, a compression test block is reserved for each group to ensure that the influence of the hydration temperature rise inhibitor on the concrete strength is within the control range.

[0108] Table 12 shows the data summary of hydration heat release and reduction rate at different ages and 28d compressive strength ratio of 7 groups of mortars formed according to the dosage in Table 11 in step S1 of Example 2.

[0109] Table 12 Mortar hydration heat release and reduction rate

[0110]

[0111]

[0112] Table 12 shows the effect of different dosages of hydration temperature rise inhibitor on cement hydration efficiency and strength. It can be seen that with the increase of the dosage of hydration temperature rise inhibitor, the hydration heat release of cement at 3d / 7d decreases successively, and the 28d mortar compressive strength also decreases accordingly. According to the "Concrete Hydration Temperature Rise Inhibitor" (JC / T 2608-2021), the 24h hydration heat reduction rate is ≥30%, and the 7d hydration heat reduction rate is ≤15%. In the present invention, when the hydration heat temperature rise is suppressed to 1.0-2.0%, the specification requirements are met, and the 28d compressive strength ratio is greater than 90%, and the influence on strength is also within the control range.

[0113] Comprehensively consider the hydration control and strength guarantee of hydration temperature rise inhibitors, that is, excessive hydration temperature rise inhibitors can greatly reduce the early hydration heat release rate and heat release, but it is very likely to cause slow strength development of concrete in the later stage due to over-addition, so the amount of hydration temperature rise inhibitor should not be too high. Therefore, with temperature control as the goal, reduce the risk of shrinkage cracking of concrete structure, and suppress hydration heat temperature rise at 1.0-2.0%, and the optimal dosage is 2.0%.

[0114] In this embodiment, the calcium-magnesium component ratio and the magnesium component activity value of the calcium-magnesium composite expansion agent are determined as follows:

[0115] Table 12 Calcium-magnesium composite expansion agent ratio

[0116] Serial number serial number CaO: Light-burned MgO 1 C4M6-150s 4:6 2 C5M5-150s 5:5 3 C6M4-150s 6:4 4 C7M3-150s 7:3 5 C8M2-150s 8:2 6 C6M4-50s 6:4 7 C6M4-100s 6:4 8 C6M4-180s 6:4 9 C6M4-230s 6:4

[0117] Taking cementitious materials as the benchmark, according to the ratio of 10% calcium-magnesium expansion agent, 200% standard sand and 40% water, 607.5g benchmark cement, 67.5g calcium-magnesium expansion agent, 1350.0g standard sand and 270.0g water were weighed and mixed evenly by a mortar mixer. The calcium-magnesium composite expansion agent was formed into 9 groups of test blocks according to the ratio in Table 12. Each group of test blocks consisted of 3 mortar specimens with a size of 40mm×40mm×140mm. The specimens needed to be cured under standard conditions to measure the restricted expansion rate at different ages.

[0118] Table 13 Restricted expansion rate of mortar with different calcium-magnesium composite ratios (%)

[0119]

[0120] Table 13 shows the influence of different calcium-magnesium composite expansion agent ratios on expansion performance. From the comparison of numbers 1, 2, 3, 4 and 5 in Table 13, it can be seen that with the increase of the CaO ratio, the 7d early limited expansion rate gradually increases. When the CaO ratio is greater than 50%, the 7d limited expansion rate of the calcium-magnesium composite expansion agent is greater than 3.5%, which meets the specification requirements of "Calcium-magnesium composite expansion agent for concrete" (T / CECS 10082-2022). However, when the CaO content is greater than 70%, the early expansion volume of 7d is large, the later expansion volume is insufficient, and the limited expansion rate at 28d is even lower than 0.0%, such as C8M2-150s, which does not meet the relevant specification requirements. Therefore, it is appropriate to have 50% to 70% CaO and 30% to 50% light-burned MgO in the calcium-magnesium composite expansion agent. In addition, comparing 3, 6, 7, 8 and 9, the ratio of calcium expander to magnesium expander was 6:4, and the reaction activity value of light-burned magnesium expander was changed to compare the expansion amount and expansion history. From the expansion amount, the 7d early restricted expansion rate of groups 3, 6, 7, 8 and 9 was greater than 3.5%, but with the increase of the reaction activity value of light-burned magnesium oxide, the early expansion amount of 7d gradually decreased, among which C6M4-230s had the weakest early expansion amount. From the expansion history, the smaller the reaction activity value of light-burned magnesium oxide, the faster the early reaction speed, and the greater the early expansion, while the larger the reaction activity value, the slower the early reaction speed. The chemical reaction is mainly concentrated in the middle and late stages for expansion compensation and shrinkage. For example, the expansion rate of C6M4-50s becomes negative at 28d, the expansion rate of C6M4-100s becomes negative at 56d, the expansion rate of C6M4-150s is always positive, and the expansion rate of C6M4-180s becomes negative at 90d. The magnesium oxide reaction activity value of C6M4-230s is 230s, and the reaction speed is extremely slow, which fails to achieve the role of expansion compensation and shrinkage. Therefore, the expansion rate becomes negative at 28d. According to the shrinkage characteristics of concrete, the shrinkage deformation curve of concrete usually has a convergence trend after 28d, and the deformation rate slows down. Based on the purpose of concrete deformation history regulation, it is required that concrete can still be stably in a positive deformation (that is, micro-expansion) state at 28d, so the reaction activity value of light-burned high-activity MgO is 100-180s.

[0121] As a specific implementation case of the present invention, according to the needs of the project, a group of calcium-magnesium composite expansion agents with better expansion process control were selected, namely C6M4-150s, that is, the ratio of CaO: light-burned MgO is 6:4, and the best light-burned MgO reaction activity value is 150s.

[0122] In this embodiment, the dosage of the calcium-magnesium composite expansion agent is determined as follows:

[0123] Table 14 Dosage of calcium-magnesium composite expansion agent

[0124] Serial number serial number Calcium magnesium composite expansion agent dosage 1 C6M4-150s-0% 0% 2 C6M4-150s-4% 4.0% 3 C6M4-150s-6% 6.0% 4 C6M4-150s-8% 8.0% 5 C6M4-150s-10% 10.0% 6 C6M4-150s-12% 12.0%

[0125] Based on the amount of cementitious materials, the calcium-magnesium composite expansive agent, 200% standard sand and 40% water are weighed and mixed according to the ratio shown in Table 14, that is, 1350.0g standard sand and 270.0g water are weighed. The ratio of CaO and 150s light-burned MgO in the calcium-magnesium composite expansive agent is 6:4, and the dosage of the calcium-magnesium composite expansive agent is 0, 4.0%, 6.0%, 8.0%, 10.0% and 12.0%. The six groups of proportions are weighed, that is, 0g, 27g, 40.5g, 54g, 67.5g, and 81g of calcium-magnesium composite expansive agent, and 675g, 648g, 634.5g, 621g, 607.5g, and 594g of cement are weighed respectively, and mixed and stirred evenly to prepare 6 groups of mortar limited expansion specimens with different dosages of calcium-magnesium composite expansive agent, which are cured under standard conditions to measure the limited expansion rate at different ages.

[0126] Table 15 Restricted expansion rate of mortar with different calcium and magnesium composite content (%)

[0127]

[0128]

[0129] Table 15 shows the effect of different calcium-magnesium composite dosages on the expansion performance based on C6M4-150s. When the dosage is 0%, it can be seen that the expansion value of the specimen is negative and is in a state of continuous contraction. As the dosage increases, the limited expansion rate increases successively. According to the provisions of "Calcium-magnesium composite expansion agent for concrete" (T / CECS 10082-2022), the limited expansion rate of 7d should be greater than 3.5%, and the limited expansion rate of 28d should be greater than 0. The requirements are met when the dosage is greater than 6% in the present invention, but it is found in the observation of the specimen that when the dosage exceeds 10%, such as No. 6, the surface of the specimen has fine cracks on the surface due to excessive expansion. Based on safety and economic considerations, the dosage range of calcium-magnesium composite expansion agent should be controlled at 6% to 10%, and as a specific implementation case of the present invention, according to the needs of a certain project, the optimal dosage is 10%.

[0130] In this embodiment, the cementitious material system and the mix ratio are determined as follows:

[0131] In order to control the cracking of railway tunnel concrete and make it easier to use in engineering projects, the cementitious system was optimized and the idea of ​​using two mineral admixtures (fly ash and slag powder) in combination with a concrete hydration temperature rise inhibitor and a calcium-magnesium composite expansion agent was determined.

[0132] According to research, on the basis of meeting the strength requirements. In terms of reducing the temperature rise of concrete, as the amount of mineral admixtures increases, the adiabatic temperature rise value of concrete gradually decreases. The amount of mineral admixtures should be between 30% and 50%. If the amount is too low, the temperature drop effect is not obvious. If the amount is too high, the strength cannot be guaranteed. From the perspective of shrinkage deformation, fly ash and slag powder can reduce the expansion of the expansion agent to a certain extent, but overall, the slag powder has a slightly greater impact. Therefore, after comprehensive consideration, the final ratio of fly ash to slag powder is 3:1.

[0133] In a certain engineering case, the concrete mix ratio is as shown in Table 15. The cement used is P·Ⅱ42.5 silicate cement, the fly ash is F-class Ⅱ fly ash, the slag powder is S95 slag powder, the sand is II zone medium sand, and the stone is 5-25mm continuous grading. The reference concrete is conventional concrete, and the crack-resistant concrete is optimized based on the reference concrete mix ratio according to the concrete calculation and evaluation performance of Example 1, wherein the amount of hydration temperature rise inhibitor is determined according to CTRI2.0, that is, 2%. The amount of calcium-magnesium composite expansion agent is 10%, wherein the ratio of CaO and light-burned MgO is determined according to C6M4-150s, that is, the ratio of CaO to 150s light-burned MgO is 6:4.

[0134] Table 16 Concrete mix ratio (Kg / m 3 )

[0135]

[0136]

[0137] According to the mix ratio in Table 16, adiabatic temperature rise test and autogenous shrinkage test were carried out respectively. The specific test results are shown in Table 17.

[0138] Table 17 Performance test of concrete with different performance

[0139]

[0140] Table 17 shows the performance comparison between the benchmark concrete and the crack-resistant concrete. After comprehensive comparison, the crack-resistant concrete meets the concrete performance working condition requirements in Table 10 of Implementation Case 1, with an adiabatic temperature rise value of no more than 45°C and a 28d autogenous shrinkage strain value of no less than +150με.

[0141] In summary, the best mix ratio of crack-resistant concrete is: 450-500 kg / m 3 , sand 665~785kg / m 3 , crushed stone 1030~1190kg / m 3 , water 145~180kg / m 3 and water reducing agent 8~12kg / m 3Among them, the cementitious material contains 2% hydration temperature rise inhibitor, 10% calcium magnesium composite expansion agent, 30-50% fly ash and slag powder in a mass ratio of 3:1, and the rest is cement.

[0142] In this embodiment, the demoulding and curing methods are determined as follows:

[0143] According to the anti-cracking concrete shown in Implementation Case 6, 6 groups of tunnel lining solid structure cracking conditions with different curing processes were cast and compared. The concrete temperature entering the mold was controlled at 28°C, the slump was controlled at 180-220mm, and the air content was 4%-6%. However, the curing methods were respectively: demolding after 1 day + no curing, demolding after 3 days + no curing, demolding after 3 days + watering curing, demolding after 3 days + geotextile curing, demolding after 5 days + watering curing, and demolding after 5 days + geotextile curing. In addition, concrete strength tests were carried out on concrete strength test blocks formed under the same conditions in each group.

[0144] Table 18 Appearance and strength of crack-resistant concrete under different demoulding and curing conditions

[0145]

[0146]

[0147] Combined with Table 18, it can be seen that on the basis of using crack-resistant concrete, extending the demolding time can better ensure the strength development and prevent the appearance of surface microcracks caused by early water evaporation, which is beneficial to improving the durability of the lining structure. If moisturizing and sprinkling curing are carried out on the basis of further extending the demolding time, the appearance of surface microcracks can be completely avoided, and the effect is better. Considering the convenience and feasibility of the embodiment, the optimal demolding time and curing method of concrete is 3d demolding and then 14d sprinkling and moisturizing curing.

[0148] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for controlling cracking of tunnel cast lining concrete, characterized in that: The following steps are also included: Determine the material parameters, mechanical parameters, thermal parameters, structural parameters and environmental parameters, and establish a finite element calculation model for temperature stress simulation according to the tunnel lining structure dimensions based on the coupling of multiple factors including concrete temperature stress shrinkage, concrete autogenous shrinkage and invert rigidity constraint; The lining concrete cracking risk coefficient corresponding to the optimal combination of different working condition parameters is analyzed by the temperature stress simulation finite element calculation model, so as to select the optimal combination of different working condition parameters with the cracking risk coefficient less than the cracking threshold value, wherein the working condition parameters include the adiabatic temperature rise, the autogenous shrinkage strain value, the mold entry temperature, and the demolding time and post-demolding curing process, which characterize the demolding curing process; According to the adiabatic temperature rise and autogenous shrinkage strain values ​​that characterize the performance of concrete in the working condition parameters, the hydration temperature rise inhibitor, calcium-magnesium composite expansion agent, mineral admixture, cement, sand and gravel and water are mixed and stirred in a certain proportion to obtain anti-cracking concrete that meets the concrete performance requirements under the optimization of different working condition parameters simulated by the model; After the tunnel invert and the invert filling layer are constructed, the mold entry temperature in the control working condition parameters is adjusted to pour the prepared crack-resistant concrete onto the invert at one time to form a lining concrete layer; After the anti-cracking concrete is poured, the formwork is removed and the post-formwork moisturizing curing is carried out according to the parameters of the formwork removal time and post-formwork curing that characterize the formwork removal and curing process.

2. The crack control method of tunnel cast lining concrete according to claim 1, characterized in that: The anti-cracking concrete comprises the following components by mass percentage: 450-500 parts of cementitious materials, 665-785 parts of sand, 1030-1190 parts of crushed stone and 145-180 parts of water; The gelling material comprises the following components by mass percentage: 1-2% hydration temperature rise inhibitor, 6-10% calcium-magnesium composite expansion agent, 30-50% mineral admixture, and the rest is cement.

3. The crack control method for tunnel cast lining concrete according to claim 2, characterized in that: The gelling material comprises: The cement is P·Ⅱ42.5 silicate cement; Fly ash is Class F II or above; The slag powder is S95 grade slag powder; The hydration temperature rise inhibitor has a cement hydration heat reduction rate of ≥30% 24 hours after initial setting and a cement hydration heat reduction rate of ≤15% 7 days after initial setting; The calcium-magnesium composite expansion agent comprises the following components by mass percentage: 50% to 70% of CaO and 30% to 50% of light-burned MgO, wherein the reaction activity value of the light-burned MgO is 100 to 180s.

4. The crack control method for tunnel cast lining concrete according to claim 3, characterized in that: The mass ratio of fly ash to slag powder in the mineral admixture is 3:

1.

5. The crack control method for tunnel cast lining concrete according to claim 4, characterized in that: The mold entry temperature is ≤28°C, the slump of the crack-resistant concrete is controlled to be 180-220mm, and the air content is 4%-6%.

6. The crack control method for tunnel cast lining concrete according to any one of claims 1 to 4, characterized in that: The cracking threshold is controlled within 0.7.

Citation Information

Patent Citations

  • A method for permanent repair of tunnel lining cracks using UHPC material

    CN113217014B

  • Underwater drilling device for leaking stoppage of tunnel concrete lining cracks and operation method of underwater drilling device

    CN114809920A

  • Crack of tunnel lining maintenance device

    CN206801582U

  • Structure for treating tunnel lining crack water seepage

    CN215718948U

Cited By

  • Tunnel secondary lining concrete anti-crack additive and construction and acceptance method

    CN119859030A

  • A kind of anti-cracking additive for secondary lining concrete of tunnel, construction and acceptance method

    CN119859030B

  • Intrinsic self-prestress ECC material, surface layer structure prepared from intrinsic self-prestress ECC material and application of intrinsic self-prestress ECC material

    CN119912226A